(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
This study focused on the usefulness of kitchen utensils made out of recycled coconut shells and how this can lessen plastic usage in every household. The study also helped the students to become creative and resourceful because Accountancy, Business, and Management (ABM) Strand students are inclined to the business world, it will be easy for them to sell this product and market all the products made from the process of recycling coconut shell because they have confidence and knowledge in terms of marketing. The researcher used the qualitative method by using the descriptive research design. This study involved 50 selected respondents from Grade 12 ABMStrand students. Seven variables in terms of the usefulness of recycling a coconut shell, such as to save money, it can be a business, functional kitchen tools, decrease in plastic usage, well-recycled, usefulness, and creativeness, were considered. The results of the study showed that more and more students were becoming interested in recycling; not only did they gain new knowledge, lessen their expenses, made themselves more productive and creative, it also helped lessen pollution brought by the improper use of plastic. The respondents of the study indicated that making do-it-yourself kitchen utensils made out of coconut shells is attractive. They agreed that it can also be used in long term. They can also make a business out of it. It will display the resourceful and creativeness of the individual; these products are sustainable because coconut tree is found everywhere in the country.